Analisis Faktor-Faktor Penentu Pengambilan Keputusan Pembelian Benih Padi Inbrida Varietas Unggul di Kecamatan Pekalongan Kabupaten Lampung Timur: indonesia - Khoirrinabila, Aulia; Dwi Sayekti, Wuryaningsih; Riantini, Maya (Politeknik Negeri Lampung, 2023)
Rice seeds are one of the factors that influence rice production and play an important role in the success of rice production. The many types of superior varieties of rice seeds have an impact on farmers' attitudes in purchasing superior varieties of rice seeds. The aim of this research is to determine farmers' purchasing patterns and decision-making processes, as well as the determining factors in farmers' purchasing decisions for inbred rice seeds in Pekalongan District. This research method is a survey method. The research was carried out in Jojog Village and Adijaya Village, Pekalongan District with a total of 90 respondents. Research analysis methods include descriptive analysis, fishbein multiattribute model, and logit analysis. Farmers' motivation in farming is to gain profits from sources of information, namely farmer groups. Evaluation considerations in purchasing inbred rice seeds are quality and marketability. Planned purchase of rice seeds with varieties Ciherang (78.89%), Inpari 32 (20%), and IR 64 (1.11%). Farmers are satisfied with superior inbred varieties of rice seeds. Farmers' attitudes show that the yield potential attribute gets the highest attitude value. Factors determining the decision to purchase inbred rice seeds of the Ciherang variety include age, land area, length of farming, grain price, farmers' attitudes, and reference groups such as farmer groups.